Penyuluhan Hukum tentang Kesadaran Hukum Masyarakat dalam Memahami Sengketa Pemindahan Kepemilikan Hak Ulayat Adat di Desa Lereng Kecamatan Kuok – Kabupaten Kampar: Pengabdian - Ratna Riyanti; Prayudi Saputra, Rian; Hafiz Sutrisno; Yuli Heriyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the problem of disputes over the transfer of customary land rights in Lereng Village, Kuok District, Kampar Regency, with a focus on increasing public legal awareness. The existence of customary law communities in Indonesia is recognized, including their customary rights, in accordance with Article 18B of the 1945 Constitution and related laws and regulations. However, the lack of understanding of positive law and customary law, as well as applicable procedures, is often the cause of disputes. Through legal counseling activities carried out on June 2, 2025 by the Faculty of Law, Pahlawan Tuanku Tambusai University, the community, especially traditional leaders and local residents, showed an increase in understanding regarding the meaning and position of customary rights in the national legal system, the legal procedures for transferring customary rights, and the legal risks of transferring rights that are not in accordance with the mechanism. It was found that disputes often arise due to ignorance of legal procedures and the absence of official documentation. Therefore, this counseling emphasizes the importance of involving the authorities (notaries, BPN, customary institutions, village officials) and making written documents to avoid future disputes.